2016
DOI: 10.1017/s0958344015000257
|View full text |Cite
|
Sign up to set email alerts
|

Corpus-based learning of Cantonese for Mandarin speakers

Abstract: This article presents the first study on using a parallel corpus to teach Cantonese, the variety of Chinese spoken in Hong Kong. We evaluated this approach with Mandarin-speaking undergraduate students at the beginner level. Exploiting their knowledge of Mandarin, a closely related language, the students studied Cantonese with authentic material in a Cantonese-Mandarin parallel corpus, transcribed from television programs. They were given a list of Mandarin words that yield a range of possible Cantonese transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The third linguistic peculiarity is that, compared with Standard Chinese, which is mainly used in formal writing, Cantonese is mostly informal and colloquial. In regions such as Hong Kong, Cantonese, when used in online communication channels, including social media platforms, forums, and online chats, is more informal and colloquial compared with its use in formal writing or speech, which often contains more typos or grammatical peculiarities [15]. The informal and colloquial nature of Cantonese poses significant challenges for NLP to capture the intended sentiments.…”
Section: Overviewmentioning
confidence: 99%
“…The third linguistic peculiarity is that, compared with Standard Chinese, which is mainly used in formal writing, Cantonese is mostly informal and colloquial. In regions such as Hong Kong, Cantonese, when used in online communication channels, including social media platforms, forums, and online chats, is more informal and colloquial compared with its use in formal writing or speech, which often contains more typos or grammatical peculiarities [15]. The informal and colloquial nature of Cantonese poses significant challenges for NLP to capture the intended sentiments.…”
Section: Overviewmentioning
confidence: 99%
“…Finally, and importantly, for the readership of this journal, there has been growing empirical evidence that DDL works not only for English but also for LOTEs: Catalan (Marco & van Lawick, 2015), Chinese (e.g., Chen, Wu, Yang, & Pan, 2016;Wong & Lee, 2016); Czech (Osolsobě & Vališová, 2012), French (e.g., Chambers & O'Sullivan, 2004), German (e.g., Ortner & Weber, 2018;Rets, 2017;Vyatkina, 2016aVyatkina, , 2016b, Italian (e.g., Kennedy & Miceli, 2001, and Spanish (e.g., Benavides, 2015). See the appendix for resources for working with DDL in these languages.…”
Section: Obstacles To Wider Ddl Implementationmentioning
confidence: 99%
“…Previous studies have shown that MT helps reduce the cognitive burden of translations (Baraniello et al, 2016) and encourages self-directed learning (Godwin- Jones, 2015;Wong & Lee, 2016). At the same time, there are still ongoing debates among educators as to whether MT use by learners should constitute cheating (Jolly & Luiane, 2022), or if it turns learners into mere passive recipients of information (Innes, 2019).…”
Section: Introductionmentioning
confidence: 99%